Host-Dependent Clustering of Campylobacter Strains From Small Mammals in Finland - Olkkola, Satu; Rossi, Mirko; Jaakkonen, Anniina; Simola, Maria; Tikkanen, Jouni; Hakkinen, Marjaana; Tuominen, Pirkko; Huitu, Otso; Niemimaa, Jukka; Henttonen, Heikki; Kivistö, Rauni (Frontiers in Microbiology, 2021)
Small mammals are known to carry Campylobacter spp.; however, little is known about the genotypes and their role in human infections. We studied intestinal content from small wild mammals collected in their natural habitats in Finland in 2010–2017, and in close proximity to 40 pig or cattle farms in 2017. The animals were trapped using traditional Finnish metal snap traps. Campylobacter spp. were isolated from the intestinal content using direct plating on mCCDA. A total of 19% of the captured wild animals (n = 577) and 41% of the pooled farm samples (n = 227) were positive for C. jejuni, which was the only Campylobacter species identified. The highest prevalence occurred in yellow-necked mice (Apodemus flavicollis) and bank voles (Myodes glareolus) which carried Campylobacter spp. in 66.3 and 63.9% of the farm samples and 41.5 and 24.4% of individual animals trapped from natural habitats, respectively. Interestingly, all house mouse (Mus musculus) and shrew (Sorex spp.) samples were negative for Campylobacter spp. C. jejuni isolates (n = 145) were further characterized by whole-genome sequencing. Core genome multilocus sequence typing (cgMLST) clustering showed that mouse and vole strains were separated from the rest of the C. jejuni population (636 and 671 allelic differences, 94 and 99% of core loci, respectively). Very little or no alleles were shared with C. jejuni genomes described earlier from livestock or human isolates. FastANI results further indicated that C. jejuni strains from voles are likely to represent a new previously undescribed species or subspecies of Campylobacter. Core-genome phylogeny showed that there was no difference between isolates originating from the farm and wild captured animals. Instead, the phylogeny followed the host species-association. There was some evidence (one strain each) of livestock-associated C. jejuni occurring in a farm-caught A. flavicollis and a brown rat (Rattus norvegicus), indicating that although small mammals may not be the original reservoir of Campylobacter colonizing livestock, they may sporadically carry C. jejuni strains occurring mainly in livestock and be associated with disease in humans.